Su Pierre-François Biancolelli detto Dominique: lo stato dell’arte e una commedia rappresentata in provincia - Guardenti, Renzo (Drammaturgia, 2024)
Pierre-François Biancolelli was one of the most important exponents of Franco-Italian comic theater in early 18th-century Paris, distinguishing as an actor, playwright and company director. The essay reviews the state of research dedicated to him and focuses on the comedy La Promenade de Rennes ou la Motte à Madame represented and published in Rennes in 1709, the first representative example of the dramaturgical-spectacular and editorial strategies undertaken by Biancolelli and intended for audiences in the French province.